Kidney stone disease increases the risk of cardiovascular events - Yuxuan Chen; XueWen Liao (PLoS ONE, 2025)
Introduction Kidney stone disease is associated with numerous cardiovascular risk factors. However, the findings across studies are non-uniformly consistent, and the control of confounding variables remains suboptimal. This study aimed to investigate the association between kidney stone and cardiovascular disease. Methods We conducted an observational study using data from the National Health and Nutrition Examination Survey conducted between 2007 and 2010. Weighted multivariable-adjusted logistic regression was used to evaluate the association between kidney stones and cardiovascular event risk. Moreover, in observational studies, Mendelian randomization (MR) was applied to avoid reverse causality and reduce the influence of potential confounding factors. Inverse-variance weighted (IVW) was the main analytical method. Results After controlling for cardiovascular and kidney stone risk factors among 7210 US adults, along with other potential confounding variables, patients with kidney stones exhibited a significantly elevated risk of acute myocardial infarction (AMI) (odds ratio [OR], 1.88 [95% confidence interval [CI], 1.09–3.26], P < 0.05). However, a non-significant association was observed with heart failure, hypertension, or stroke. MR analyses further indicated that genetically predicted kidney stones were causally associated with an increased risk of coronary heart disease (OR, 1.07 [95% CI, 1.04–1.53], P = 0.028), myocardial infarction (OR, 1.08 [95% CI,1.02–1.15], P = 0.015), hypertension (OR 1.01 [95% CI, 1.00–1.02], P = 0.042) and ischemic stroke (OR, 0.86 [95% CI, 0.75–0.98], P = 0.022) in IVW models, with non-significant associations detected for heart failure. Conclusions The occurrence of kidney stones has been associated with an elevated risk of myocardial infarction within the context of cardiovascular events. However, cross-sectional analyses yield results that are inconsistent with those obtained from Mendelian randomization analyses regarding outcomes such as heart failure, hypertension, and stroke.